The Impact of Green Management and Technology in Electrical and Electronics Manufacturing in Business Sustainability in Malaysia - Md Taib, Mohd Yazid; Mohamed Udin, Zulkifli; Abdul Ghani, Abdullah (Penerbit UTM Press, 2015)
This paper is aim to investigating the impact of green management (GM) and technology (GT)in the electrical and electronics industry. Environmental issues, pollution and corruption due to wrong doing. This questionnaire survey-based paper was a cross sectional approach. The samples were derived by simple random sampling from the Federation of Malaysian Manufacturing report of 2013/2014. A pilot test data of 40 respondents was collected and tested using factor analysis, construct validity and reliability. The data obtained and used in this survey were self-reporting by respondent from the respective industry. The outcome, suggested that GM and GT should be holistically implemented. This paper contributed to the body of knowledge through identifying the relationship between GM and GT practices in Business Sustainability